2020
DOI: 10.1080/10942912.2020.1833916
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Momordica charantia L on blood pressure: a systematic review and meta- analysis of randomized clinical trials

Abstract: Several reports have indicated a positive effect of Momordica charantia (MC) on blood pressure (BP); nevertheless, these findings have been controversial. Therefore, a systematic review and meta-analysis of randomized controlled trials (RCTs) were aimed to investigate the effects of MC supplementation on BP. PubMed, Scopus, ISI Web of Science, and Cochrane library databases were searched (up to June 2020) to identify RCTs investigating the effects of Momordica charantia supplementation on systolic blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
(93 reference statements)
1
9
0
Order By: Relevance
“…There was moderate-quality evidence showing significantly decreased DBP with blueberry [ 122 ], SBP and DBP with beetroot [ 123 ], berries [ 124 ], cactus pear [ 45 ], and pomegranate [ 125 ] intakes. There was moderate-quality evidence showing nonsignificantly decreased SBP with blueberry [ 122 ], SBP and DBP with bitter melon [ 126 ] and strawberry (SBP) intakes [ 127 ]. Low-quality evidence was available for garlic [ 128 ], ginger [ 129 ], cranberry (SBP) [ 130 ], grapefruit (SBP) [ 131 ], strawberry (DBP) [ 127 ], sour cherry (DBP) [ 132 ], Goji berry [ 133 ], kiwi fruit [ 134 ], fruit juice [ 81 ], orange juice [ 135 ], fruits and vegetables [ 136 ], and tomato [ 137 ], and very-low-quality evidence for 100% fruit juice [ 138 ] and aronia berry [ 139 ].…”
Section: Resultsmentioning
confidence: 99%
“…There was moderate-quality evidence showing significantly decreased DBP with blueberry [ 122 ], SBP and DBP with beetroot [ 123 ], berries [ 124 ], cactus pear [ 45 ], and pomegranate [ 125 ] intakes. There was moderate-quality evidence showing nonsignificantly decreased SBP with blueberry [ 122 ], SBP and DBP with bitter melon [ 126 ] and strawberry (SBP) intakes [ 127 ]. Low-quality evidence was available for garlic [ 128 ], ginger [ 129 ], cranberry (SBP) [ 130 ], grapefruit (SBP) [ 131 ], strawberry (DBP) [ 127 ], sour cherry (DBP) [ 132 ], Goji berry [ 133 ], kiwi fruit [ 134 ], fruit juice [ 81 ], orange juice [ 135 ], fruits and vegetables [ 136 ], and tomato [ 137 ], and very-low-quality evidence for 100% fruit juice [ 138 ] and aronia berry [ 139 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in agreement with a statistical expert and based on relevant references (12,13), we commonly used correlation coefficient (r) = 0.5 (14)(15)(16)(17) as an average to minimize the bias of estimates. In addition, it is noteworthy that all of our methodology protocols and approaches were officially registered with PROSPERO (https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=213987) (1).…”
Section: Dear Editormentioning
confidence: 99%
“…In the last five years, numerous review articles have been published about bitter melon chemical compounds ( 37 , 38 ), nutritional value ( 39 , 40 ), and pharmacological actions ( 36 , 41 43 ), but only a few are with meta-analysis. Jandari et al performed a systematic review and meta-analysis of randomized clinical trials regarding the effect of bitter melon on blood pressure ( 44 ), Cortez-Navarrete et al reviewed the metabolic effects of bitter melon reported in clinical trials ( 45 ), but without performing a meta-analysis, while Peter et al evaluated the efficacy in lowering the elevated plasma glucose level in diabetes mellitus ( 46 ). The present systematic review and meta-analysis aimed to evaluate the effect of bitter melon on metabolic syndrome parameters.…”
Section: Introductionmentioning
confidence: 99%